Advancing conceptualisation of university entrepreneurial ecosystems: The role of knowledge-intensive entrepreneurial firms. (May 2019) - Link, Albert N; Sarala, Riikka M
University entrepreneurial ecosystems are increasingly important in facilitating innovation and entrepreneurial opportunities in today's knowledge-based economies. However, we have an incomplete understanding of the demand side of university entrepreneurial ecosystems regarding the role of the entrepreneurial firm as the key user of university knowledge. We propose that use of university knowledge positively influences entrepreneurial firm performance and that the entrepreneurial firm's resources and capabilities facilitate its ability to create value from university knowledge. We test our hypotheses on survey data of 3853 knowledge-intensive entrepreneurial firms from 10 European countries. Our study contributes to an increased understanding of the economic, societal and technological contributions of universities by empirically illustrating the role of firm resources and capabilities as moderators of value in university entrepreneurial ecosystems.